2013
DOI: 10.1021/ar3003267
|View full text |Cite
|
Sign up to set email alerts
|

The Increasingly Complex Mechanism of HMG-CoA Reductase

Abstract: CONSPECTUS The seven decades of research on the mechanism of HMG-CoA Reductase (HMGR) provided a detailed reaction pathway for what is one of the most biomedically important and mechanistically most complex enzymes. HMGR is the target of statins that are prescribed to improve the quality of life of millions of people worldwide and, more recently, has been identified as a target for the development of antimicrobial agents. The impact of advances in diverse research areas, such as molecular biology and computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 49 publications
1
65
1
3
Order By: Relevance
“…3-Hydroxy-3-methyl coenzyme A reductase (HMG-CoA reductase) is the rate-limiting enzyme for cholesterol synthesis. 24) Inhibiting its activity could reduce the LDL-c synthesis. But what is different is our study has found serum LDL levels decreased and LDLR gene expressions was also significantly reduced after paeoniflorin administration, which is inconsistent with the usual findings.…”
Section: Discussionmentioning
confidence: 99%
“…3-Hydroxy-3-methyl coenzyme A reductase (HMG-CoA reductase) is the rate-limiting enzyme for cholesterol synthesis. 24) Inhibiting its activity could reduce the LDL-c synthesis. But what is different is our study has found serum LDL levels decreased and LDLR gene expressions was also significantly reduced after paeoniflorin administration, which is inconsistent with the usual findings.…”
Section: Discussionmentioning
confidence: 99%
“…While in terms of reaction catalyzed, QueF nitrile reductases share commonalities with other four-electron reductases, such as 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (29)(30)(31) and the non-ribosomal peptide synthetase module myxalamid reductase (32,33), that use NAD(P)H to convert thioester-activated forms of carboxylic acids into primary alcohols via an aldehyde intermediate, they are individuated strongly from these other enzymes in having to deal with a highly decomposition-prone intermediate. The central role of intermediate sequestration in the QueF mechanism seems to be reflected in the fact that structural devices used to keep a firm grip on the imine intermediate are likewise involved directly in the catalytic events of the enzymatic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…HMGR (EC 1.1.1.34) catalyzes an irreversible conversion of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) into MVA, which is the key ratecontrolling and first committed step of isopentenyl diphosphate (IPP) biosynthesis via the MVA pathway (Chappell 1995 (Kato-Emori et al 2001;Haines et al 2013). HMGR is an enzyme used in the initial stages of isoprenoid biosynthesisgenes encoding HMGRs have been isolated and characterized from many species since 1996 (Korth et al 1997;Maldonado-Mendoza et al 1997;KatoEmori et al 2001;Liao et al 2004;Shen et al 2006;Wang et al 2007;Lin et al 2009;Cao et al 2010;Dai et al 2011;Akhtar et al 2013).…”
Section: -Hydroxy-3-methylglutaryl Coenzyme a Reductase (Hmgr)mentioning
confidence: 99%